SOME ASPECTS OF THE EVOLUTIVE BIOLOGY OF CHILEAN SPECIES OF TEPHRITIDAE (DIPTERA) (Acta Entomológica Chilena, 2022)
There are about 4.000 described species of Thephritidae (Díptera). The origin of this family isunknown, ñor are the phylogenetic relations among the species and the mechanisms which generateand maintain the genetic variation in natural populations well understood. Sludies in evolutionarybiology have shown that different subfamilies may be separated and characterized according to theirhosts, genetic distance and chromosomal mechanisms of sex determination. For some chilean speciestheir phylogenetic relationships has been established through the electrophoretic method. Thisanalysis indicates a corelalion between the genetic identity of these flies and the taxonomicsimilarity of their plant hosts, which suggests a parallel evolution between insects and plants. Thispaper presents a list of species, genera and subfamilies of Tephritidae in Chile for which plants areknown. These hosts also are Usted. Also the citotaxonomy of the Thephritidae is review, withemphasis on the neotropical and specially the chilean species which I have previously studied, toestablish the similarities and differences among species of various subfamilies.In Chile the subfamily Tephritinae is the one with the most genera and species, which always areassocialed with plants of the family Compositae. Regarding the chromosomal mechanisms of sexdetermination this group is characterized by a ZW chromosomic system, or the sex chromosomesapparently are isomorphic. On the other hand, the subfamily Trypetinae offers a reduced taxonomicdiversity, infesting groups of plants of other families. Flies in this subfamily have a XY mechanismof sex determination, which corresponds to the oldest chromosomic sex determination system in thedíptera.